Correlation analysis between risk factors and mucositis oral in head and neck cancer patients undergoing radiotherapy - Dewi, Tenny Setiani; Lefaan, Yannie Febby; Susilawati, Sri; Kusumadjati, Adji; Arief, Erry Mochamad (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Radiotherapy is a cancer therapy that uses ionizing radiation to damage cancer cells. Ionizing radiation in the head and neck area can disrupt the function and integrity of the oral mucosa and cause oral mucositis. In Bandung, the prevalence and risk factors of oral mucositis in head and neck cancer (HNC) patients undergoing radiotherapy have not been studied. Some textbooks claim that the prevalence of radiotherapy-induced oral mucositis in HNC patients occurs at almost 100%. Various risk factors associated with oral mucositis have been studied, giving significantly different results. This research analyzes the correlation between risk factors and mucositis oral in head and neck cancer patients undergoing radiotherapy. Methods: This research is a cross-sectional retrospective study with secondary data from medical records of HNC patients at RSHS from January 2015 until December 2019. A consecutive sampling method was used to collect the data that match the Inclusion criteria, including diagnosis of HNC(ICD-10), receiving radiotherapy from the first cycle until the last cycle; having a complete medical record following variables (location of HNC coding by ICD-10, gender, age, education level, smoking habit, the cycle of radiotherapy, oral treatment, body mass index, and comorbid disease). All data were then analyzed using Spearman correlation. Result: 171 medical records showed 59 patients had oral mucositis after radiotherapy. 26.9% male and 7.6% female, with susceptible age 40-60 years. Analysis of the Spearman correlation, there is a significant relationship between body mass index (BMI) (ρ = 0,001), smoking habits (ρ = 0,001), and radiotherapy cycles (ρ = 0.001). Conclusion: There is a correlation between risk factors of oral mucositis in HNC patients undergoing radiotherapy in RSHS, including body mass index (BMI), smoking habits, and radiotherapy cycles.Keywords: Head and neck cancer; oral mucositis; prevalence; risk factor; retrospective study